PENGARUH LITERASI KEUANGAN DAN SIKAP RISIKO TERHADAP KEPUTUSAN INVESTASI SYARIAH GENERASI MILENIAL: PENDEKATAN SEM-PLS DI KABUPATEN JOMBANG - Beni Sucipto (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2023)
This study aims to examine the influence of financial literacy and risk attitude on sharia investment decisions among Millennials in Jombang Regency. The increasing participation of young investors in the Islamic capital market highlights the need for a more comprehensive understanding of the cognitive and psychological factors that influence sharia-compliant investment decision-making. This research employs a quantitative approach with an explanatory research design through a survey of 80 Millennial respondents who have experience or interest in Islamic investment instruments. Purposive sampling was applied, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS version 8.0. The results indicate that financial literacy has a positive and significant effect on sharia investment decisions (β = 0.438; p < 0.001), and risk attitude also has a positive and significant effect (β = 0.334; p < 0.001). The coefficient of determination (R² = 0.417) shows that both variables explain 41.7% of the variance in investment decisions, indicating moderate explanatory power. The predictive relevance value (Q² = 0.398) further confirms the model’s strong predictive capability. These findings suggest that sharia investment decisions are simultaneously influenced by rational factors (financial knowledge) and psychological factors (risk tolerance).